Keterlibatan Konsumen Berdasarkan Efektivitas Iklan Terhadap Loyalitas Merek Pada Produk SIM Card IM3 di Wilayah Sidoarjo - Handayani, Wiwik (Jurnal Aplikasi Manajemen, 2009)
Progressively increase consumer of HP (Hand Phone) at this time, make celluler provider in this country compete to give programs can make consumer interest. Like a IM3 which give telephone and SMS tarif cheap to consumer. IM3 many use advertising like a print and electronic to introduce program they are to consumer celluler. But often advertising present good by IM3 or other celluler provider too abundant, so that make consumer swallow the bait. in this fact, need consumer involvement to searching more information about program an offer by celluler provider, so that consumer don't feel swallow the bait. With consumer involvement in searching information about brand, expect consumer can know good or bad a program from celluler provider, to be make brand loyalty from consumer to product from celluler provider. Because that the purpose from this research is to know consumer involvement to SIM card brand trough advertising so that can make brand loyalty. Sample which use in this research is consumer IM3's SIM card of old age minimum 16 year which buying repeat voucher more from 10 time and use more from 1 year. Data's gathering do by submit list of question to respondent (questioner). Analysis used in research is Structural Equation Modeling (SEM). The result from this research is can know that advertising effectiveness influential positive to consumer involvement. So also with consumer involvement influential positive to brand loyalty.